2005
DOI: 10.1086/427820
|View full text |Cite
|
Sign up to set email alerts
|

Lag‐Luminosity Relationship for Interband Lags between Variations inB,V,R, andIBands in Active Galactic Nuclei

Abstract: We determine interband lags between variations in the B band and variations in the V, R, and I bands for 14 active galactic nuclei observed at the Crimean Astrophysical Observatory. The computed lags range from tenths of a day to several days, and it is positive (that is, V, R, and I bands lag behind the B band) in most cases, except for a few cases for the V filter. In some cases, the lag is greater than zero, with more than 3 confidence. The lag is systematically less for the V filter than for the red filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
240
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(270 citation statements)
references
References 13 publications
26
240
3
1
Order By: Relevance
“…It is possible that our assumption of continuum emission originating at r = 0 could cause us to underestimate M BH , although it is also worth noting that NGC 5548 was in an exceptional state during the course of this RM campaign and the emission-line time delays were all shorter than predicted from the radius-luminosity relation (Pei et al 2017). Time delays between the EUV and optical of varying quality and significance have been reported by several other studies as well (Collier et al 1998;Sergeev et al 2005;McHardy et al 2014;Shappee et al 2014;Edelson et al 2015), suggesting that the situation is not unique.…”
Section: Systematic Uncertainties From Assumptions Of the Modelmentioning
confidence: 55%
“…It is possible that our assumption of continuum emission originating at r = 0 could cause us to underestimate M BH , although it is also worth noting that NGC 5548 was in an exceptional state during the course of this RM campaign and the emission-line time delays were all shorter than predicted from the radius-luminosity relation (Pei et al 2017). Time delays between the EUV and optical of varying quality and significance have been reported by several other studies as well (Collier et al 1998;Sergeev et al 2005;McHardy et al 2014;Shappee et al 2014;Edelson et al 2015), suggesting that the situation is not unique.…”
Section: Systematic Uncertainties From Assumptions Of the Modelmentioning
confidence: 55%
“…However, wavelengths shorter than ∼3200Å are inaccessible from the ground, so the rest-frame optical continuum is often used as a proxy for the ionizing source in low-redshift AGNs. Although the far-UV and optical continua have been shown to vary almost simultaneously in some cases (e.g., Clavel et al 1991;Reichert et al 1994;Korista et al 1995;Wanders et al 1997), more recent high-cadence studies have found that the optical continuum can lag the UV continuum by up to a few days (Collier et al 1998;Sergeev et al 2005;McHardy et al 2014;Shappee et al 2014;Edelson et al 2015;Fausnaugh et al 2016). This can significantly affect the measured broadline lag if the BLR has a characteristic radius on the order of light-days.…”
Section: Introductionmentioning
confidence: 99%
“…Quasar accretion disks cannot be spatially resolved with ordinary telescopes, so we have been forced to test accretion physics through time variability (e.g., Vanden Berk et al 2004;Sergeev et al 2005;Cackett et al 2007) and spectral modeling (e.g., Sun & Malkan 1989;Collin et al 2002;Bonning et al 2007). One notable success is the use of reverberation mapping (e.g., Peterson et al 2004) of quasar broad-line emission to calibrate the relation between emission line widths and black hole masses.…”
Section: Introductionmentioning
confidence: 99%
“…One notable success is the use of reverberation mapping (e.g., Peterson et al 2004) of quasar broad-line emission to calibrate the relation between emission line widths and black hole masses. The line emission, though, comes from scales much larger than the accretion disk, and attempts to use similar methods on the continuum emission have had limited success, largely because quasars show little optical variability on the disk light-crossing timescale (Collin et al 2002;Sergeev et al 2005).…”
Section: Introductionmentioning
confidence: 99%